2005
DOI: 10.1270/jsbbs.55.425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytological Diversity in Cultivated Rice Oryza sativa Subspecies japonica and indica

Abstract: In cultivated rice Oryza sativa, although physiological and molecular biological studies have demonstrated the existence of a high intra-species diversity, there are few reports related to the molecular cytological diversity. To examine the molecular cytological diversity in O. sativa, a tandem repeat-sequence Os48 was visualized using fluorescence in situ hybridization (FISH) in various rice varieties. Diversity was reflected by differences in the number of FISH signals. The number of loci detected was almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Although FISH has revealed intraspecific variation in the number and position of rDNA sites in plants, these changes generally occurred among different accessions and were conserved within an accession, as described for rice [Nakayama, 2005] and for most common bean accessions [Pedrosa-Harand et al, 2006]. In this later species, however, one wild accession presented a heteromorphism for the 45S rDNA similar to that observed in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Although FISH has revealed intraspecific variation in the number and position of rDNA sites in plants, these changes generally occurred among different accessions and were conserved within an accession, as described for rice [Nakayama, 2005] and for most common bean accessions [Pedrosa-Harand et al, 2006]. In this later species, however, one wild accession presented a heteromorphism for the 45S rDNA similar to that observed in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…The origin of temperate japonica varieties from tropical japonicas has also been proposed from other studies (Garris et al 2005;Londo et al 2006). Other explanations, such as independent origins of temperate and tropical japonicas from as yet unidentified O. rufipogon with Type F cp, may be less likely because of the relative lack of diversity in japonica varieties compared with indica varieties (Ishii et al 1988;Kadowaki et al 1988;Nakayama 2005). Cheng et al (2002) reported that the 2 ecotypes of O. sativa, indica and japonica, are distinguishable, almost exclusively, by the presence or absence of p-SINE1 members, which are nuclear genome sequences.…”
Section: Japonicamentioning
confidence: 62%